Trends in cardiovascular risk factors across levels of education in a general population: is the educational gap increasing? The Tromsø study 1994–2008. Issue 8 (27th March 2014) - Eggen, Anne Elise; Mathiesen, Ellisiv B; Wilsgaard, Tom; Jacobsen, Bjarne K; Njølstad, Inger
Abstract : Background: To describe trends in cardiovascular risk factors and change over time across education levels, and study the influence from medicine use and gender. Methods: Data from participants (30–74 years) of the Tromsø Study in 1994–1995 (n=22 108) and in 2007–2008 (n=11 565). Blood samples, measurements and self-reported educational level and medicine use were collected. Results: Differences in risk factor levels across education groups were persistent for all risk factors over time, with a more unfavourable pattern in the lowest education group. The exception was cholesterol, with the reduction being largest in the lowest educated, resulting in weakened educational trends over time. While a significant educational trend in cholesterol persisted among the non-users of lipid-lowering drugs (LLD), no educational trend in cholesterol was found among the LLD users in 2007–2008. The strongest educational trends were found for daily smoking and Body Mass Index (BMI). In 2007–2008 the odds for being a smoker were five times higher among the lowest educated compared to the highest educated. In men, the odds for being in the highest quintile of the BMI distribution were, in 2007–2008, almost doubled in the lowest compared to the highest educated. The lowest educated women had 6.2 mm Hg higher mean systolic blood pressure than the highly educated, mean BMI of 26.4 kg/m 2 and smoking prevalence of 37.7%. Conclusions: The difference across education groups for cholesterol levels decreased, while the educational gap persisted over time for the other risk factors. Use of LLD seemed to contribute to the reduction of social differences in cholesterol levels.